2010
DOI: 10.1073/pnas.1007026107
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing structure-activity relationship to engineer a cisplatin nanoparticle for enhanced antitumor efficacy

Abstract: Cisplatin is a first line chemotherapy for most types of cancer. However, its use is dose-limited due to severe nephrotoxicity. Here we report the rational engineering of a novel nanoplatinate inspired by the mechanisms underlying cisplatin bioactivation. We engineered a novel polymer, glucosamine-functionalized polyisobutylene-maleic acid, where platinum (Pt) can be complexed to the monomeric units using a monocarboxylato and an O → Pt coordinate bond. We show that at a unique platinum to polymer ratio, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 26 publications
7
86
3
Order By: Relevance
“…It has been suggested that internalization of CDDP-loaded carriers is a key factor in increasing the drug's efficacy. 35,36 Therefore, the enhanced cytotoxicity of the PLGA nanocarriers in comparison to free drug may also be explained by the effective endocytosis exhibited by both types of NPs. The CS-CDDP NPs demonstrated relatively similar cytotoxicity to the U-CDDP NPs, although they released ~10% less drug over the 72 h period, possibly, because they released less of the drug into the cell medium and more intracellularly.…”
mentioning
confidence: 99%
“…It has been suggested that internalization of CDDP-loaded carriers is a key factor in increasing the drug's efficacy. 35,36 Therefore, the enhanced cytotoxicity of the PLGA nanocarriers in comparison to free drug may also be explained by the effective endocytosis exhibited by both types of NPs. The CS-CDDP NPs demonstrated relatively similar cytotoxicity to the U-CDDP NPs, although they released ~10% less drug over the 72 h period, possibly, because they released less of the drug into the cell medium and more intracellularly.…”
mentioning
confidence: 99%
“…Yet, no improvement in antitumor activity of ∼110 nm PEG-poly (N-amino acidyl)-aspartamidecisplatin micelles relative to free cisplatin was reported. Recent work by Paraskar et al 33 also utilized aggressive cancer models (subcutaneous Lewis lung carcinoma and 4T1 breast cancer xenografts) to evaluate the antitumor activity of 80-140 nm cisplatin-loaded poly-isobutylene-maleic acid nanoparticles. However, no improvement in antitumor activity relative to equidose free cisplatin was observed.…”
mentioning
confidence: 99%
“…PIMA contains reactive anhydride functional groups that can be easily conjugated to a wide range of drugs and other reactive moieties under mild reaction conditions and can be used for conjugating more than one agent for multiplexing studies. Recently, we reported that the coordination complex between platinum (II) and PIMA could enable the self-assembly into nanostructures that exhibited greater antitumor efficacy with reduced systemic toxicity compared with cisplatin (41,42).…”
Section: Design and Synthesis Of The Reporter And Effector Componentsmentioning
confidence: 99%